2004
DOI: 10.1074/jbc.m310404200
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Erythropoietin Gene Regulation by GATA-4

Abstract: Erythropoietin production switches from fetal liver to adult kidney during development. GATA transcription factors 2 and 3 could be involved in modulating this switch, because they were shown to negatively regulate erythropoietin gene transcription through a promoter proximal GATA site. Herein, we analyzed the role of several GATA factors in the regulation of the erythropoietin gene in human liver and in hepatoma cells. Although GATA-3 expression in hepatocytes increases during human development, erythropoieti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 64 publications
2
84
2
Order By: Relevance
“…1). The murine Gata4 siRNA sequence is almost identical to a human GATA4 siRNA sequence, which effectively reduced GATA4 in human hepatoma cells (Dame et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1). The murine Gata4 siRNA sequence is almost identical to a human GATA4 siRNA sequence, which effectively reduced GATA4 in human hepatoma cells (Dame et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The Gata4 siRNA sequence (TCTCGATATGTTTGATGAC) is almost identical to a human GATA4 siRNA (NCBI accession no. L34357; nt 852-870 relative to the transcription start site: TCTCGATATGTTTGACGAC) that has previously been shown to efficiently reduce GATA4 expression in human hepatoma Hep3B cells (Dame et al 2004). Normal expression levels of Gata2 mRNA demonstrated that Gata4 siRNA is specific.…”
Section: In Vitro Efficacy Of Gata4 Rnaimentioning
confidence: 99%
See 1 more Smart Citation
“…GATA-4 is expressed exclusively in hepatocytes and binds strongly to this GATA motif, enhancing Epo expression (Dame et al 2004). The marked reduction in expression of hepatic GATA-4 following birth is likely an important contributor to the switch in Epo production from liver to kidney (Dame et al 2004).…”
Section: Regulation Of the Epo Genementioning
confidence: 99%
“…Dame et al (59) reported that GATA-4 is critically involved in EPO gene expression and may be responsible for the switch in the site of EPO production from the fetal liver to the adult kidney. In addition, GATA-2 inhibits EPO gene transcription by binding to the GATA sequence on the EPO promoter, thereby leading to downregulation of EPO mRNA expression and subsequent EPO synthesis (60).…”
Section: Gata Inhibitionmentioning
confidence: 99%